White Light Generating Molecular Materials: Correlation Between the Amorphous/Crystalline Structure and Nonlinear Optical Properties. Issue 6 (26th May 2022) - Haust, Johannes; Belz, Jürgen; Müller, Marius; Danilo Klee, Benjamin; Link Vasco, Jonathan; Hüppe, Franziska; Rojas Léon, Irán; Christmann, Jan; Beyer, Andreas; Dehnen, Stefanie; Rosemann, Nils W.; Pilgrim, Wolf‐Christian; et al.
Abstract: Amorphous materials are an integral part of today's technology‐they commonly are performant and versatile in integration. Consequently, future applications increasingly aim to harvest the potential of the amorphous state. Establishing its structure‐property relationship, however, is inherently challenging using diffraction‐based techniques yet is extremely desirable for developing advanced functionalities. In this article, we introduce a set of transmission electron microscopy‐based techniques to locally quantify the structure of a material. This unique approach allows to clearly identify the spatial distribution of amorphous and crystalline regions and to quantify atomic arrangements of amorphous regions of a representative model system. We study an ensemble of well‐defined, functionalized adamantane‐type cluster molecules exhibiting exceptionally promising nonlinear optical properties of unclear origin. The nanoscopic structure for three model compounds ([(PhSn)4 S6 ], [(NpSn)4 S6 ], [(CpSn)4 S6 ]) correlates with their characteristic optical responses. These results highlight the advantageous properties of amorphous molecular materials when understanding the microscopic origin. Abstract : Knowledge of the amorphous/crystalline structure of adamantane‐type molecular clusters is critical to understand their exceptional nonlinear optical properties. In this work we quantify the intra‐ and intermolecular structure of three model compounds by different transmission electron microscopy based techniques and correlate the results with their nonlinear optical response.